Annual Review of Indian Primary Securities Market : 2013-14 - Gupta, Ambrish (Indian Journal of Research in Capital Markets, 2014)
This paper carried out an annual review of Indian primary securities market for the year 2013-14. Towards this purpose, it reviewed the public issue mobilization of the past 5 years vis-a-vis Y2013-14, carried out an investigation into the policy initiatives taken during the year by the Securities and Exchange Board of India for the development of the market, carried out a demographic analysis of the resources mobilized in the market, analyzed the returns from the IPOs, and presented a holistic view of the market during 2013-14. The study found that the activity in the market, though better than the previous year, continues to be lacklustre. However, the outlook for the rest of the current year seems to be optimistic.